Low-temperature alkali corrosion induced growth of nanosheet layers on NiTi alloy and their corrosion behavior and biological responses. (September 2021) - Zhao, Ya; Bai, Long; Sun, Yonghua; Yao, Xiaohong; Huang, Xiaobo; Hang, Ruiqiang; Huang, Di
Highlights: Nanosheet layers were grown on NiTi alloy by low-temperature alkali corrosion. The nanosheet layers were composed of TiO2, Na4 TiO4, and Ni(OH)2 . The nanosheet layers could be grown in 1−15 M NaOH solution at 25−80 °C. The nanosheet layer showed good corrosion resistance, antibacterial ability, and cytocompatibility. Abstract: We report on a reliable and cost-effective method (alkali corrosion) to construct nanosheet layers on nearly equiatomic nickel-titanium (NiTi) alloy, which only needs to immerse it in1−15 M NaOH solution at low temperature (4–80 ℃). The layers are mainly composed of TiO2, Na4 TiO4, and Ni(OH)2, and Ni content increases with NaOH concentration. The layers exhibit potent antibacterial ability and can promote endothelial spreading and proliferation, although the corrosion resistance is slightly decreased due to significantly increased specific surface area. Good corrosion resistance, antibacterial ability, and cytocompatibility render the nanosheet layers promising as biomedical coatings of the NiTi alloy.